A test of the efficiency of futures markets in commodities - Sanjeev Gupta; Thomas Mayer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
The role of the futures markets in stabilising spot prices has been widely discussed. However, the success of these markets in performing the stabilising function critically depends on whether they are efficient (Fama 181, page 383) in the sense that the futures prices fully reflect the available information. The question of futures market efficiency has assumed greater relevance in view of the recent UNCTAD proposals to stabilise the prices of primary commodities exported mainly by the developing countries. The Integrated Programme for Commodities put forward by the Group of 77 at UNCTAD IV in 1976 calls for the establishment of buffer stocks for 18 such commodities. The recent developments show, however, that the political as well as the economic success of the UNCTAD schemes is rather doubtful. Under these circumstances, the feasibility of other efficient market oriented alternatives for stabilising commodity prices needs to be examined. Further, it could be argued that theoretically the case for buffer stocks for stabilising prices rests in part on the lack of sufficient and rational speculators in these markets. For, if futures markets reflect the available information and provide efficient forecasts of the future spot prices, the rationale for UNCTAD schemes is somewhat weakened. In this paper, we test the efficiency of futures markets for five of the commodities in the UNCTAD list. At the outset, we discuss various approaches for testing the efficiency of futures markets. A semi-strong' test is then performed. The data, the models and the results are presented in sections III through V. The concluding comments and the economic implications are discussed in the last section.
Keywords: 330